An Analysis of Students' Ability in Translating Idiom on Narrative Text - Riskaulina Sinaga (Universitas Maritim Raja Ali Haji, 2021)
The purpose of this research is to find out the student’s ability in translating idiom on narrative text written by them as investigated by the researcher. This research belongs to descriptive qualitative research. The subject of this research involved twenty students of fourth semester of English Department Students University Maritim Raja Ali Haji. The instrument used a test. The test that has given is short answer, which the students are asked to find how many idioms that the student found on narrative text given by the researcher. After finding the idiom, the students were asked to translate into Indonesian with meaning correctly. The result of this research reveals that the students’ ability to find and translated idiom is still not accurate in translation. The students’ only found a few of idioms from 20 idioms that given by the researcher which were contained on narrative text. The problem that arises when the results are analyzed is inability of students to translate with the meaning correctly so that some students translate word by word. Keywords: Translating, idiom, narrative text